The Impact of investment in Research and Development on the Economic Growth in Serbia - Kutlaca, Djuro; Sestic, Suncica; Jelic, Svetlana; Popovic-Pantic, Sanja (Industrija, 2020)
The main objective of this paper is to examine the impact of investment in research and development on economic growth in the Republic of Serbia, expressed through the correlation of this and other macroeconomic aggregates. A variety of statistical and econometric techniques of variables and time series analysis are employed. In order to quantify the contribution of investments in research and development to the GDP real growth, initially data series at current prices are converted in real terms, applying previously calculated composite deflator for research and development. Based on these data, estimated for the period 1995-2015, the contribution of R&D investments to the GDP real growth is explicitly shown and expressed in percentage points. Also, the latest available data since 2016. up to 2018. Have been presented in order to show the trend in this area. The empirical results achieved in the study reveal a strong interdependence among the R&D expenditures and economic performance at the national level in Serbia. Based on these findings, a statistically significant causality relationship oriented from GDP real growth to research and development activity is confirmed. As real economic activities and growth rate increase, R&D must also increase for sustainability. However, the causality in the opposite direction cannot be verified.